Strategic Electronic Government Procurement : Strategic Planning Guide - Asian Development Bank; Inter-American Development Bank; World Bank (World Bank, Washington, DC, 2014)
Many countries have discovered that the transition to e-government, and all the benefits that this entails, can require the extensive re-engineering of public sector management, service design and delivery, legislation and even community expectations. E-government is a reform program which exploits the potential of online technology, but is not delivered merely through the design, acquisition and application of this technology. Like other parts of an e-government program, implementing e-GP is a reform strategy, and like any reform strategy, will be developed, customized and owned by each jurisdiction if it is to succeed. An e-GP implementation strategy is sensitive to all of the elements that distinguish one jurisdiction from another including management and leadership culture, regulations, skills and expertise, etcetera. This guide is intended to provide an awareness of the issues and critical success factors that will generally be found in any successful e-GP strategy and is aimed at assisting jurisdictions and organizations develop their own implementation strategy for this sensitive and high value activity of government.